Translation and validation of body image instruments: An addendum to Swami and Barron (2019) in the form of frequently asked questions. (June 2021) - Swami, Viren; Todd, Jennifer; Barron, David
Highlights: Update on test adaptation recommendations and guidelines in Swami and Barron (2019). Methods for ensuring semantic equivalence are reviewed. Methods for ensuring measurement equivalence are reviewed. Methods are applicable to body image and other social science constructs. Abstract: Test adaptation – the translation and validation of source instruments for use in new social identity groups – plays a vital role in body image research. Previously, Swami and Barron (2019) developed a set of good practice recommendations and reporting guidelines for the test adaptation of body image instruments. However, a number of issues in that article were not covered in depth and new issues have emerged as a result of developments in theory and practice. Here, we offer an addendum to Swami and Barron in the form of frequently asked questions. Issues discussed in this article include various methods for achieving good translations, the appropriateness of revising instrument components prior to empirical analyses, determining the number of factors to extract in exploratory factor analyses (EFA), and the usefulness of EFA versus confirmatory factor analyses (CFA) in determining factorial validity. We also cover methods of analyses that have been infrequently utilised by body image scholars, including exploratory structural equation modelling (ESEM), bifactor model analyses, and various methods for establish measurement invariance. When read as an addendum to Swami and Barron, we hope this article helps to clarify issues of importance for body image researchers interested in conducting test adaptation work.